INTERACTION IN A THERMODYNAMICALLY CLOSED ROCK-WATER SYSTEM AS A CLUE TO THE GENESIS OF CHLORIDE GROUNDWATERS - Ryzhenko B.N.; Krainov S.R. (My University, 2001)
Thermodynamic simulation was conducted for the systems of the main rock types and seawater of different concentration degrees. The simulation results indicate that the interaction between both meteoric waters and seawaters (that did not undergo significant evaporative concentration) with crystalline rocks (and sedimentary salt-free rocks) results in Cl-Na(Ca) waters with mineralization of up to n × 10 g/l. An analogous interaction with salt-bearing sedimentary rocks gives rise to Cl-Na-Mg(Ca) brines with salinities of n × 102 g/kg of H2O. Chloride Na, Ca, and Mg brines of compositions analogous to those of natural waters result from the interaction of seawater of high concentration degrees with crystalline or sedimentary rocks. It is demonstrated that Cl-bearing minerals of the rocks play a determining role in the metamorphism of meteoric or seawaters in rock-water systems.